Refinement of a Hardy–Littlewood–Pólya-type inequality for powers of self-adjoint operators in a Hilbert space - Bilichenko, R. O.; Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The well-known Taikov’s refined versions of the Hardy – Littlewood – Pólya inequality for the L_2-norms of intermediate derivatives of a function defined on the real axis are generalized to the case of powers of self-adjoint operators in a Hilbert space.